Multimodal functional imaging and clinical correlates of pain regions in chronic low-back pain patients treated with spinal cord stimulation: a pilot study - Shamli Oghli, Yazan; Ashok, Arjun; Glener, Steven; Ailes, Isaiah; Syed, Mashaal; Kang, Ki Chang; Naghizadehkashani, Sara; Fayed, Islam; Mohamed, Feroze B.; Talekar, Kiran; Krisa, Laura; Wu, Chengyuan; et al. (Frontiers in Neuroimaging, 2024)
Objective: Spinal cord stimulation (SCS) is an invasive treatment option for patients suffering from chronic low-back pain (cLBP). It is an effective treatment which has been shown to reduce pain and increase quality of life in patients. However, activation of pain processing regions of cLBP patients receiving SCS has not been assessed using objective, quantitative functional imaging techniques. The purpose of the present study was to compare quantitative resting-state (rs)-fMRI and arterial spin labeling (ASL) measures between SCS patient and healthy controls, and to correlate clinical measures with quantitative multimodal imaging indices in pain regions. Methods: Multi-delay 3D GRASE pseudo-continuous ASL and rs-fMRI data was acquired in five patients post-SCS with cLBP and five healthy controls. Three ASL measures and four rsfMRI measures were derived and normalized into MNI space and smoothed. Averaged values for each measure from a pain atlas were extracted and compared between patients and controls. Clinical pain scores assessing intensity, sensitization, catastrophizing, as well as others assessing global pain effects (sleep quality, disability, anxiety and depression) were obtained in patients and correlated to pain regions using linear regression analysis. Results: Arterial transit time derived from ASL and several rs-fMRI measures were significantly different in patients in regions involved with sensation (primary somatosensory cortex, ventral posterolateral thalamus; VPL), pain input (posterior short gyrus of the insula; PS), cognition (dorsolateral prefrontal cortex; DLPC, posterior cingulate cortex; PCC), and fear/stress response (hippocampus, hypothalamus). Unidimensional pain rating and sensitization scores were linearly associated to PS, VPL, DLPC, PCC, and/or amygdala activity in cLBP patients. Conclusion: The present results provide evidence that ASL and rs-fMRI can contrast functional activation in pain regions of cLBP patients receiving SCS and healthy subjects, and they can be associated with clinical pain evaluations as quantitative assessment tools.